How to deal with international terrorism - Tim Krieger; Daniel Meierrieks (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2014)
Since the 9/11 attacks on New York and Washington D.C., the fight against international terrorism has been a dominant issue in the political arena. Policy-makers (still) face the challenge to develop sound strategies for fighting this type of terrorist activity. Unfortunately, there is no universal strategy to counter terrorism. This is partly due to the diverse and clandestine nature of terrorist groups, and partly due to misperceptions, lack of precise knowledge as well as divergent interests and prioritization on part of policy-makers. The present chapter aims at providing a systematic overview on how to deal with (international) terrorism, taking on a law and economics perspective. More specifically, we will examine how the rule of law - both nationally and internationally (i.e., in terms of the international law) - interacts with international terrorism and how it can be sustained under the extreme conditions of terrorism.
Keywords: 330